Practical implementation of H-infinity control for fuel cell-interleaved boost converter. (2nd January 2020) - Hammoudi, Mohamed Yacine; Saadi, Ramzi; Cardoso, Antonio J Marques; Benbouzid, Mohamed El Hachemi; Sahraoui, Mohamed
ABSTRACT: This paper presents a non-isolated DC–DC converter for fuel-cell electric vehicle applications. An H-infinity control, based on mixed sensitivity, applied to a three-phase interleaved boost converter, is proposed. This controller is intended for an outer voltage loop and an inner current loop, to ensure a high stability, especially of the dynamic responses, under any operating conditions. The proposed H-infinity controller for the fuel cell system is implemented in a digital signal processor, thus ensuring both excellent reference tracking and disturbance rejection properties.